Heritability of Horn Size in Thinhorn Sheep - Sim, Zijian; Coltman, David W. (Frontiers in Genetics, 2019)
Understanding the genetic basis of fitness-related trait variation has long been of great interest to evolutionary biologist. Secondary sexual characteristics, such as horns in bovids, are particularly intriguing since they can be potentially affected by both natural and sexual Understanding the genetic basis of fitness-related trait variation has long been of great interest to evolutionary biologist. Secondary sexual characteristics, such as horns in bovids, are particularly intriguing since they can be potentially affected by both natural and sexual selection. Until recently however, the study of fitness-related quantitative trait variation in wild species has been hampered by a lack of genomic resources, pedigree and/or phenotype data. Recent innovations in genomic technologies have enabled wildlife researchers to perform marker-based relatedness estimation and acquire adequate loci density, enabling both the “top-down” approach of quantitative genetics and the “bottom-up” approach of association studies to describe the genetic basis of fitness-related traits. Here we combine a cross species application of the OvineHD BeadChip, and horn measurements (horn length, base circumference and volume) from harvested thinhorn sheep to examine the heritability and to perform a genome-wide SNP association study of horn size in the species. Thinhorn sheep are mountain ungulates that reside in mountainous regions of northwestern North America. Thinhorn sheep males grow massive horns that determine the social rank and mating success. We found horn length, base circumference and volume to be moderately heritable and two loci to be suggestively associated with horn length.